Introduction to product design and development for engineers - Jamnia, Ali, 1961- (Boca Raton, FL : CRC Press/Taylor & Francis Group, 2018)
Introduction to Product Design and Development for Engineers provides guidelines and best practices for the design, development, and evaluation of engineered products. Created to serve fourth year undergraduate students in Engineering Design modules with a required project, the text covers the entire product design process and product life-cycle, from the initial concept to the design and development stages, and through to product testing, design documentation, manufacturability, marketing, and sustainability. Reflecting the author's long career as a design engineer, this text will also serve as a practical guide for students working on their capstone design projects--
Includes bibliographical references and index.
HB
Keywords: Product design